Iron(III)-Catalyzed Prins Cyclization towards the Synthesis of trans-Fused Bicyclic Tetrahydropyrans - Pérez, Sixto J.; Miranda, Pedro O.; Cruz, Daniel A.; Fernández, Israel; Martín, Víctor S.; Padrón, Juan I. (Synthesis, 2015)
trans-Fused bicyclic tetrahydropyrans have been synthesized through an intramolecular Prins cyclization catalyzed by iron(III). The cyclization process is stereoselective, leading exclusively to an all-cis configuration in the newly generated ring. This useful methodology allows for easy access to a variety of bicyclic ethers present in a wide range of bioactive natural products. Remarkably, the cyclization reaction works well when more challenging aldehydes bearing a functional group, such as a double bond or an acetate, are used. In addition, we present a computational study which rationalizes the results and explains the complete cis stereoselectivity in the newly formed tetrahydropyran ring.
Keywords: iron; cyclic ethers; sustainable metal catalysis; bicyclic tetrahydropyrans; Prins cyclization